No evidence of association between blastocyst aneuploidy and morphokinetic assessment in a selected population of poor-prognosis patients: a longitudinal cohort study. Issue 1 (January 2015) - Rienzi, L.; Capalbo, A.; Stoppa, M.; Romano, S.; Maggiulli, R.; Albricci, L.; Scarica, C.; Farcomeni, A.; Vajta, G.; Ubaldi, F.M.
Abstract Recent studies involving a limited number of patients have indicated a correlation between aneuploidy and various morphokinetic parameters during preimplantation development. The results among different groups, however, have been inconsistent in identifying the parameters that are able to predict chromosomal abnormalities. The aim of this study was to investigate whether aneuploidy of human blastocysts was detectable by specific morphokinetic parameters in patients at increased risk of aneuploidy because of advanced maternal age, history of unsuccessful IVF treatments, or both. A longitudinal cohort study was conducted using 455 blastocysts from 138 patients. Morphokinetic features of preimplantation development were detected in a timelapse incubator. Blastocysts were subjected to trophectodermal biopsy and comprehensive chromosomal screening. Analyses were conducted by means of logistic mixed-effects models, with a subject-specific intercept. No statistical correlation between 16 commonly detected morphokinetic characteristics of in-vitro embryo development and aneuploidy was found. Results suggest that morphokinetic characteristics cannot be used to select euploid blastocysts in poor-prognosis patients regarded as candidates for pre-implantation genetic screening.